The national wildlife refuges : - Fischman, Robert L. (Island Press, 2003)
The National Wildlife Refuges provides a comprehensive examination of the laws and policies governing management of the national wildlife refuges, offering for the first time a practical description and analysis of the management regime outlined in the 1997 National Wildlife Refuge System Improvement Act. The 1997 act is the first new statute governing a system of federal public lands enacted since the 1970s. The evolution of law governing the refuge system parallels broader trends in public land management and environmental protection, making the refuge system a valuable case study for those interested in environmental management, policy, and law.